A comparative study of short-term efficacy and safety for thyroid micropapillary carcinoma patients after microwave ablation or surgery - Jianming Li; Yujiang Liu; Jibin Liu; Peipei Yang; Xiangdong Hu; Linxue Qian (International Journal of Hyperthermia, 2019)
Background: Although papillary thyroid microcarcinoma (PTMC) has a high incidence and excellent clinical outcome, debate continues as to the therapeutic approach that would be most appropriate after confirming the diagnosis. Methods: We retrospectively analyzed the medical records of 311 patients with T1aN0M0 PTMC between January 2013 and September 2018. In all, 168 underwent microwave ablation (MWA), and 143 underwent surgery. MWA was performed using extensive ablation with hydrodissection. The surgery comprised thyroid lobectomy (TL) with unilateral central lymph node dissection (CND). We examined clinical outcomes during mean follow-up periods of 824 ± 452 days for the TL group and 753 ± 520 days for the MWA group. Results: Postprocedural follow-up revealed that, in the MWA group, the tumors had completely disappeared in 34 patients, and the remainder were reduced to necrotic or carbonized tissue. The incidence of transient hypoparathyroidism was significantly lower in the MWA group than in the TL group (p < .001). In addition, during the follow-up, we found no statistically significant differences between the two groups (TL vs MWA) for PTMC recurrence (1 vs 2 cases), lymph node metastasis (5 vs 5 cases), or disease-free survival [2001 days (5.5 years) vs 1702 days (4.7 years)] (p = .659, p = .795, and p = .974, respectively). Conclusions: If low-risk thyroid carcinoma (i.e., T1N0M0 PTMC) is accurately diagnosed early, MWA could be a minimally invasive alternative to surgery based on our short-term follow-up regarding recurrence and the low rates of complications and disease-free survival.